Advances in the Application of Perovskite Materials - Lixiu Zhang; Luyao Mei; Kaiyang Wang; Yinhua Lv; Shuai Zhang; Yaxiao Lian; Xiaoke Liu; Zhiwei Ma; Guanjun Xiao; Qiang Liu; Shuaibo Zhai; Shengli Zhang; et al. (Nano-Micro Letters, 2023)
Highlights A comprehensive summary of the representative promising applications of metal halide perovskite materials, including traditional optoelectronic devices (solar cells, light-emitting diodes, photodetectors, lasers), and cutting-edge technologies in terms of neuromorphic devices (artificial synapses and memristors) and pressure-induced emission. For each application, the fundamentals of the field, the current progress and the remaining challenges are provided, based on the up-to-date works.